Toward Integrated Water Resources Management in Armenia - Yu, Winston; Cestti, Rita A.; Lee, Ju Young (Washington, DC: World Bank, 2014)
The proper management of water resources plays a key role in the socioeconomic development of Armenia. On average, Armenia has sufficient water resources. Taking into account all available water resources in the country, Armenia has sufficient resources to supply approximately 3,100 cubic meters per capita per year well above the typically cited Falkenmark water stress indicator of 1,700 cubic meters per capita per year. These water resources are not evenly divided in space and time with significant seasonal and annual variability in river runoff. In order to address temporal variations in river runoff, the country has built 87 dams with a total capacity of 1.4 billion cubic meters. Most of these dams are single purpose, mainly for irrigation. Armenia also has considerable groundwater resources, which play an important role in the overall water balance. About 96 percent of the water used for drinking purposes and about 40 percent of water abstracted in the country comes from groundwater. Irrigation remains the largest consumptive user.